Near-infrared image-based method for vision enhancement in monitoring structure and emission character of operating phosphor-converted white light emitting diodes - Nguyen, Quang-Khoi; Huynh, Van-Tuan; Phan, Nguyet-Thuan; Vu, Thi-Hanh-Thu; Hua, Thi-Hoang-Yen; Nguyen , Huynh-Tuan Anh (Photonics Letters of Poland, 2025)
We proposed and demonstrated a method for observing the structure of phosphor-converted white light-emitting diodes (pcW-LEDs) while operating. By incorporating infrared (IR) filters placed in front of the camera, the unclear phenomena of the pcW-LEDs structure in the image have been improved significantly compared to that without using IR filters. The NIR image is a good selection for observation of the light-emitting device during its working process without glare effect. In addition, the thermal camera was utilized to capture the temperature behavior of the white LEDs type of phosphor conformal coating under different injection currents to supplement comprehensive information. Full Text: PDF References E.F. Schubert, J.K. Kim. "Solid-State Light Sources Getting Smart", Science 308, 1274 (2005). CrossRef E.F. Schubert, Light-emitting diodes (Cambridge University Press, 2006). CrossRef Y.Y. Chang, Z.Y. Ting, C.Y. Chen, T.H. Yang, C.C. Sun. "Design of Optical Module With High Stability, High Angular Color Uniformity, and Adjustable Light Distribution for Standard Lamps", J. Disp. Technol. 10, 223 (2014). CrossRef C.C. Sun, C.Y. Chen, C.C. Chen, C.Y. Chiu, Y.N. Peng, Y.H. Wang, T.H. Yang, T.Y. Chung, C.Y. Chung. "High uniformity in angular correlated-color-temperature distribution of white LEDs from 2800K to 6500K", Opt. Express 20, 6622 (2012). CrossRef C.C. Sun, Q.K. Nguyen, T.X. Lee, S.K. Lin, C.S. Wu, T.H. Yang, Y.W. Yu. "Active thermal-fuse for stopping blue light leakage of white light-emitting diodes driven by constant current", Sci. Rep. 12, 12433 (2022). CrossRef S. Chhajed, Y. Xi, Y.-L. Li, Th. Gessmann, E. F. Schubert. "Influence of junction temperature on chromaticity and color-rendering properties of trichromatic white-light sources based on light-emitting diodes", J. Appl. Phys. 97, 054506 (2005). CrossRef J.L. Davis, K.C. Mills, G. Bobashev, K.J. Rountree, M. Lamvik, R. Yaga, C. Johnson, "Understanding chromaticity shifts in LED devices through analytical models", Microelectron. Reliab. 84, 149 (2018). CrossRef M.Y. Mehr, A. Bahrami, W.D.V. Driel, X.J. Fan, J.L. Davis, G.Q. Zhang, "Degradation of optical materials in solid-state lighting systems", Int. Mater. Rev. 65, 102 (2020). CrossRef Y.F. Su, S.Y. Yang, T.Y. Hung, C.C. Lee, K.N. Chiang, "Light degradation test and design of thermal performance for high-power light-emitting diodes", Microelectron. Reliab. 52, 794 (2012). CrossRef T.-N. Tran, V.-T. Huynh, T.-H.-T. Vu, N.-T. Phan, H.-T.-A. Nguyen, Q.-K. Nguyen, "Study of steady-state thermal model for white light LEDs thermal management application at encapsulant level", Photonics Lett. Pol., 16(1), 13 (2024). CrossRef Q.-K. Nguyen, T.-H.-T. Vu, "An Efficient Method for Simulating the Temperature Distribution in Regions Containing YAG:Ce3+ Luminescence Composites of White LED", J. Compos. Sci, 7, 301 (2023). CrossRef